Optically pumped magnetometers detect altered maximal muscle activity in neuromuscular disease - Semeia, Lorenzo; Middelmann, Thomas; Baek, Sangyeob; Sometti, Davide; Chen, Hui; Grimm, Alexander; Lerche, Holger; Martin, Pascal; Kronlage, Cornelius; Braun, Christoph; Broser, Philip; Siegel, Markus; et al. (Frontiers in Neuroscience, 2022)
Optically pumped magnetometers (OPM) are quantum sensors that enable the contactless, non-invasive measurement of biomagnetic muscle signals, i.e., magnetomyography (MMG). Due to the contactless recording, OPM-MMG might be preferable to standard electromyography (EMG) for patients with neuromuscular diseases, particularly when repetitive recordings for diagnostic and therapeutic monitoring are mandatory. OPM-MMG studies have focused on recording physiological muscle activity in healthy individuals, whereas research on neuromuscular patients with pathological altered muscle activity is non-existent. Here, we report a proof-of-principle study on the application of OPM-MMG in patients with neuromuscular diseases. Specifically, we compare the muscular activity during maximal isometric contraction of the left rectus femoris muscle in three neuromuscular patients with severe (Transthyretin Amyloidosis in combination with Pompe’s disease), mild (Charcot-Marie-Tooth disease, type 2), and without neurogenic, but myogenic, damage (Myotonia Congenita). Seven healthy young participants served as the control group. As expected, and confirmed by using simultaneous surface electromyography (sEMG), a time-series analysis revealed a dispersed interference pattern during maximal contraction with high amplitudes. Furthermore, both patients with neurogenic damage (ATTR and CMT2) showed a reduced variability of the MMG signal, quantified as the signal standard deviation of the main component of the frequency spectrum, highlighting the reduced possibility of motor unit recruitment due to the loss of motor neurons. Our results show that recording pathologically altered voluntary muscle activity with OPM-MMG is possible, paving the way for the potential use of OPM-MMG in larger studies to explore the potential benefits in clinical neurophysiology.